Pengaruh Berkesadaran Penuh (Mindfulness) terhadap Spiritualitas Mahasiswa STAB Maitreyawira Pekanbaru - Dharmaji Chowmas (Jurnal Maitreyawira, 2021)
This research is motivated by the lack of scientific studies on the effect of mindfulness on student spirituality in religious education, including Buddhist education, especially in Indonesia. Therefore, this study aims to determine the effect of mindfulness on the spirituality of STAB Maitreyawira Pekanbaru students. The research method used is a quantitative method. The population in this study were all STAB Maitreyawira students batch 2018, 2019 and 2020 with a total of 144 students. The sample in this study was 106 students. The data collection instrument is in the form of a questionnaire. The validity and reliability of the mindfulness questionnaire and the students' spirituality were tested. The normality test of the data was carried out with the Kolmogorov Smirnov test. The results of data analysis showed that there was a positive and significant influence between mindfulness on the spirituality of STAB Maitreyawira Pekanbaru students. Mindfulness provides an effective contribution of 20.49% to student spirituality. This means that 20.49% of students' spirituality can be increased through mindfulness, the remaining 79.51% can be increased through Buddhist religious ritual variables and other variables not examined in this study. So this study shows that mindfulness (X1) has a positive and significant influence individually on student spirituality (Y) STAB Maitreyawira. KATA KUNCI: Berkesadaran Penuh, Spiritualitas